(untitled) (Transactions on Additive Manufacturing Meets Medicine, 2021)
Additive manufacturing (AM) has been growing continuously over the past 20 years, enabling unprecedented tailoring to the anatomy of each patient. In Europe, custom-made devices qualify for an exemption and pass a simplified approval process. New technologies, like AM, provoke questions about the adequacy of the current regulatory framework for custom-made devices. This article addresses the regulatory requirements for such devices in Europe and discusses the implications for AM. It concludes that the legal framework for custom-made devices entails uncertainties which need to be resolved to guide manufacturers through the regulatory requirements, highlighting the specific areas of focus for AM.